The Effect of Quantum Dot Shell Structure on Fluorescence Quenching By Acridine Ligand - Linkov, P A; Vokhmintcev, K V; Samokhvalov, P S; Laronze-Cochard, M; Sapi, J; Nabiev, I R (KnE Energy, 2018)
The current strategy for the development of advanced methods of tumor treatment focuses on targeted drug delivery to tumor cells. Quantum dot (QD) - semiconductor fluorescent nanocrystal, conjugated with a pharmacological ligand, such as acridine, ensures real-time tracking of the delivery process of the active substance. However, the problem of QD fluorescence quenching caused by charge transfer can arise in the case when acridine is bound to the QD. We found that QD shell structure has a defining role on photoinduced electron transfer from QD on acridine ligand which leads to quenching of QD photoluminescence. We have found that multishell CdSe/ZnS/CdS/ZnS QD structure provides minimal reduction of photoluminescence quantum yield at minimal shell thickness compared to classical thin ZnS or “giant” shells. Thus, CdSe/ZnS/CdS/ZnS core/multishell QD could be an optimal choice for engineering of small-sized acridine-based fluorescent labels for tumor diagnosis and treatment systems. Keywords: Quantum dot, photoluminescence quenching, DNA ligand, acridine derivative.